American underdog [videorecording (DVD)] - Erwin, Jonathan D.; Cohen, David Aaron; Gunn, Jon, 1973-; Levi, Zachary, 1980-; Paquin, Anna; Blain, Ser'Darius; McGill, Bruce, 1950-; Zaller, Hayden; Kelly, Chance; Quaid, Dennis; Baldwin, Adam, 1962-; Kimlin, Kristopher S.; et al. (Lionsgate, 2022)
Tells the inspirational true story of Kurt Warner, who went from a stockboy at a grocery store to a two-time NFL MVP, Super Bowl champion, and Hall of Fame quarterback. The film centers on Warner's unique story and years of challenges and setbacks that could have derailed his aspirations to become an NFL player, but just when his dreams seemed all but out of reach, it is only with the support of his wife, Brenda and the encouragement of his family, coaches, and teammates that Warner perseveres and finds the strength to show the world the champion that he already is.